Pengaruh Integrasi Sistem Informasi Terhadap Efisiensi Administrasi Dan Pelaporan Pada Sekretariat Dinas Pemberdayaan Perempuan Perlindungan Anak, Pengendalian Penduduk Dan Keluarga Berencana Kota Surakarta - Asmarajati, Suluh; Suranto, Joko (Solidaritas, 2024)
In the modern era, governments are faced with challenges such as high accountability and limitedresources. In the digital era, the integration of information systems is important to optimizeadministration and reporting. The formulation of this research problem is whether the integrationof information systems has a significant effect on administrative and reporting efficiency at theDP3AP2KB Secretariat of Surakarta City. The purpose of this study was to examine the effect ofinformation systems integration on administrative and reporting efficiency at the DP3AP2KBSecretariat of Surakarta City. This research is expected to contribute to the development of publicadministration science, especially in improving administrative and reporting efficiency throughinformation system integration. The type of research method used is quantitative method withsaturated sampling technique. Data sources used primary and secondary data, data collectedthrough questionnaires distributed to 31 employees at the Secretariat of DP3AP2KB SurakartaCity. Data analysis was carried out in this study with simple linear regression using SPSSsoftware. Based on the results of research and discussion, it shows that the integration ofinformation systems affects the efficiency of administration and reporting at the Surakarta CityDP3AP2KB Secretariat with a positive and significant regression coefficient value, which meansthat any increase in information system integration will be followed by an increase in theefficiency of administration and reporting.Keywords: Information system integration, administrative efficiency, reporting